Enhanced recovery pathway in adult patients with spinal deformity undergoing open thoracolumbar surgery - Qingyang Huang; Lang Xiao; Shuaikang Wang; Peng Cui; Di Han; Peng Wang; Shibao Lu (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The poor prognosis of adult patients with spinal deformity following long-segment spinal fusion surgery remains a major concern. Our study aims to investigate the impact of an Enhanced Recovery After Surgery (ERAS) protocol on the prognosis of adult patients with spinal deformity. Methods This study focused on a retrospective review of a database of previous adult spinal deformity. Adult patients with spinal deformity who underwent long-segment fusion surgery from July 2016 to July 2022 were evaluated, from July 2016 to July 2019 for the pre-ERAS patient group and from July 2019 to July 2022 for the ERAS group. Demographic data, radiological sagittal parameters, and intraoperative data were collected from all patients. The length of hospital stay, postoperative complications, and 90-day readmission rates were compared between the two groups. Additionally, multivariate regression models were used to analyze the predictors of postoperative length of stay, postoperative complications, and 90-day readmission rates. Results A total of 215 patients were included in this study, 102 patients in the pre-ERAS group and 113 patients in the ERAS group. Postoperative outcomes in the ERAS group included significantly lower postoperative length of stay (LOS) (13.09 ± 4.57 vs. 11.13 ± 4.16, P = 0.001); significantly lower rate of postoperative complications (52.0% vs. 29.2%, P < 0.001) and significantly lower 90-day readmission rates (14.7% vs. 6.19%, P = 0.040). Multivariate linear regression showed that fewer ERAS (P = 0.022), later drain placement (P = 0.027), and more complications (P = 0.002) were significantly associated with longer postoperative LOS. Multivariate logistic regression showed that fewer ERAS (P = 0.015) and later drain removal (P = 0.041) were significantly associated with more complications, and more ERAS (P = 0.009), earlier postoperative LOS (P = 0.020), and earlier urinary catheter removal (P = 0.034) were significantly associated with the 90-day readmission rates. Conclusions According to the results of our study, it is necessary to implement an ERAS protocol for adult patients with spinal deformity undergoing long-segment fusion surgery. The ERAS protocol is effective in reducing postoperative hospital length of stay, incidence of surgical complications, and 90-day readmission rates.